TEACHERS' PERCEPTIONS OF REWARD AND PUNISHMENT AND ITS IMPLEMENTATION IN LEARNING AT SMP IT KHAIRUL IMAM MEDAN - Muhammad Sapii Harahap; Isnawati Isnawati (Proceeding International Seminar of Islamic Studies, 2021)
This study aims: 1) To find out how the teacher's perceptions of reward and punishment and its implementation 2) To know what are the forms of reward and punishment 3) To find out how the impact of the application of reward and punishment in learning to students at SMP IT Khairul Imam. To achieve this goal, researchers used data collection techniques by means of observation, interviews and document studies, data sources, data analysis and data validity observation that refers to qualitative research. The findings of the study show that: 1) The teacher's perception is that Broadly speaking, the teacher supports the reward and punishment that is regulated by the school in the student discipline, although the implementation of the violations committed by students does not reach the second level of violations, the average violation is only a level violation. one. So that the punishment that is carried out is only done by the teacher. 2) the forms of reward and punishment in learning are: a) there are two types of punishment, namely physical and non-physical punishment but cannot be separated from the educational context. Corporal punishment is: ordering to surround the school field, saluting the flagpole, and quoting the garbage that is still scattered around the school area. Meanwhile, non-physical punishment in the form of a teacher only gives advice and scolds the students but does not yell and say harsh words. b) There are two types of rewards, namely material and non-material prizes. The material prizes given are in the form of award stars, trophies, books, etc. to students who excel. Non-material prizes that are given in speech such as honorary praise, applause, etc. to students or students who excel. These two awards will be given witnessed by at least their classmates or in a larger scope, namely the school at the time of distribution of report cards or at events held at the school. 3) the impact of the application of reward and punishment is: a) a positive impact, that is, most students feel afraid of punishment if they violate and become motivated to change for the better and try to get prizes given by the school. b) While the impact is negative, namely the existence of some teachers and students who do not like the punishment. because they think that punishment is a bad thing that is not usually done by students. Keywords: SMP IT Khairul Imam, Reward And Punishment.